Species Diversity and Carbon Stock of Mangrove in Guiuan, Eastern Samar, Philippines - Bobon-Carnice, Pearl Aphrodite; Magalona, Ma. Melania L.; Obias, Darlene Joy A. (Academia Journal of Biology, 2023)
Mangrove forests sequester substantial amounts of atmospheric carbon dioxide, store carbon in their biomass, and have the highest carbon pool of any forest. The Philippines is one of the mangrove-rich countries, with almost 1.9% of the global mangroves. No current published works on mangroves exist in Guiuan, Eastern Samar, Philippines. This study utilized a non-destructive technique through quadrat sampling to identify and measure mangroves’ biodiversity and carbon stock. The allometric equation was applied to quantify the carbon stock and Shannon-Wiener diversity index to determine the biodiversity. Twelve species were identified from the 36 sampling plot with 10 × 10 meter. Results showed the mean species evenness of 0.28 and the Shannon-Wiener diversity value of 0.92, indicating very low diversity. The overall aboveground, belowground, total carbon stock, and CO2 sequestration of 209 t/ha, 76 t/ha, 157 t/ha, and 575 CO2 t/ha, respectively. The test revealed that comparing the six barangays regarding species diversity and carbon stocks gives no statistically significant difference of 0.032 and 0.046, respectively. Considering the estimated carbon stock and CO2 equivalent accounted from the tree biomass, the mangrove stands in Guiuan have the potential to store and sequester a large amount of carbon dioxide.